Seepage behavior and mechanical properties of two kinds of polyurethane/water glass in combined grouting experiment. (June 2023) - Wang, Pengcheng; Li, Shuchen; Li, Jinglong; Zhou, Huiying; Ma, Pengfei; Tian, Ye; Yuan, Chao; Feng, Xianda
Graphical abstract: Highlights: Developed a combined grouting experiment facility using a transparent chamber. Conducted a combined grouting experiment with foam and reinforcement grouts. Recorded evolution of combined grouting pressure and grout outline diffusion. Tested the mechanical properties of grout-gravel mixture at different locations. Analyzed the interaction between two kinds of Polyurethane/water glass grouts. Abstract: Combined grouting with multiple materials can effectively block flowing water that cannot be blocked by conventional grouting methods. Firstly, foam grouting is used to reduce the fluidity of water, and then reinforcement grouting is employed to improve the grouting effect. The traditional cement grout cannot achieve the required foamability, setting rate, and injectability. Therefore, two kinds of polyurethane/water glass grouts have been used in combined grouting experiments. In this study, we combine foam and reinforcement polyurethane/water glass to examine the interaction performance of grout seepage. We develop a visible grouting facility, including a transparent chamber and a grouting pump. We monitor the grouting pressure during the test and use a charge-coupled device camera to capture the diffusion of both grouts in the granular media. After solidification of the grouts, the samples were cored and tested to obtain the uniaxial compressive strength (UCS), porosity, and density. Our results demonstrate that the reinforcement grouting pressure increased, as compared with the foam grouting pressure, because the foam grouting blocked water and pressure conduction. The reinforcement grout intruded into the foam grout, and the UCS was improved. The higher the grouting pressure at the corresponding location of the samples, the larger the total filling ratio. The larger the volume percentage of RPU/WG, the smaller the volume percentage of FPU/WG, the greater the strength and the greater the density of the samples. The empirical strength-equivalent porosity equation is also provided in this paper. We suggest that foam grouting shall be carried out outside the stress-bearing area first, and then reinforcement grouting shall be carried out inside the stress-bearing area. This study provides a reference for the theoretical development and field application of combined grouting.